2017
DOI: 10.2147/ott.s132410
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ecotropic viral integration site-1 is a prognostic factor of lung squamous cell cancer

Abstract: AimTo explore the expression and clinical significance of ecotropic viral integration site-1 (EVI1) of lung squamous cell cancer (SCC).MethodsThe expression of EVI1 in SCC was detected by immunohistochemistry and the validation cohort was divided into EVI1 high-expression group and low-expression group according to the cutoff of immunohistochemical score. The correlations between EVI1 expression and the clinicopathological factors were analyzed by χ2 test. The relation between EVI1 expression and overall survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…In acute myeloid leukaemia, EVI1 overexpression is an independent adverse prognostic factor [22,23] . Similar results have also been reported in ICC [13] , hepatocellular carcinoma [24] , colorectal cancer [25] , prostate cancer [26] , lung cancer [27] , glioblastoma multiforme [28] and so on [29,30] . These data indicate that EVI1 plays an important role in tumour progression.…”
Section: Discussionsupporting
confidence: 86%
“…In acute myeloid leukaemia, EVI1 overexpression is an independent adverse prognostic factor [22,23] . Similar results have also been reported in ICC [13] , hepatocellular carcinoma [24] , colorectal cancer [25] , prostate cancer [26] , lung cancer [27] , glioblastoma multiforme [28] and so on [29,30] . These data indicate that EVI1 plays an important role in tumour progression.…”
Section: Discussionsupporting
confidence: 86%
“…High expression of EVI1 was significantly associated with a poorer five-year survival rate of squamous cell lung cancer patients. Moreover, EVI1 was identified as an independent prognostic factor, suggesting that EVI1 alone was enough to predict poor prognosis of squamous cell lung cancer [ 18 ]. Another study done by Wang et al [ 19 ] demonstrated EVI1 overexpression in both estrogen receptor-positive (ER +) and estrogen receptor-negative (ER −) breast carcinomas by analyzing a tissue microarray of 608 breast carcinoma patient specimens.…”
Section: Evi1 and Mds1/evi1 In Solid Tumorsmentioning
confidence: 99%
“…In addition, they identified MECOM expression as an independent prognosis marker in GBM [97]. Xu et al [18] showed that 32.32% of squamous cell lung cancer samples express a high level of EVI1. High expression of EVI1 was significantly associated with a poorer five-year survival rate of squamous cell lung cancer patients.…”
Section: Evi1 and Mds1/evi1 In Solid Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in several solid tumors, an EVI1 overexpression indicates poor survival. Such a correlation between EVI1 overexpression and a poor outcome is described, e. g., for cancers of the colon, lung, ovary, and prostate [8][9][10][11][12][13][14]. But EVI1 is not just a prognostic marker.…”
Section: Introductionmentioning
confidence: 99%